Preliminary Data from a Field Trial of the PFA-100™ System - Mammen, Eberhard F; Alshameeri, Rasheed S; Comp, Philip C (Seminars in Thrombosis and Hemostasis, 1995)
The PFA-100™ system *(Dade International Inc., Miami, FL) is a platelet function anaIyzer, the design of which is based on the technology of the Thrombostat 4000 VDG, Seeon, Germany. † It was developed to measure primary, platelet dependent hemostasis in citrated whole blood in vitro. A first pilot study was conducted with the instrument to assess performance characteristics. Healthy subjects (normals) who had not ingested any medications, and patients (abnormals) with primary, platelet-related hemostasis defects, which included users of aspirin, were studied with two test cartridges; collagen/ADP and collagen/epinephrine. Before the study certain variables were tested that ascertained that blood drawn into either 3.8% or 3.2% sodium citrate containing vacutainers (rather than syringes) could be used for testing. Tests must be performed within a five-hour time span from drawing to testing, and blood must be kept at room temperature. Normal reference values were 77–133 seconds closure times for collagen/ADP and 98-185 seconds for collagen/ epinephrine. Precision testing revealed a CV of >10% for within-day and between-day (five days) analyses on collagen/ADP cartridges and a CV of 5–14% for both runs on the collagen/epinephrine cartridges. No clinically important differences were found between measurements in the two positions of the instrument, although one follows the other. Tests on 99 normals and 70 abnormals were performed and data expressed as receiver/operator characteristics (ROC) curves that assess the combined sensitivity and specificity of a procedure. An area under the curve of 1.0 means that all samples (normals + abnormals) were accurately identified; a value of 0.5 indicates that the test is noninformative. Using collagen/ADP cartridges a value of 0.76 was found when testing 99 normals and 52 abnormals. All aspirin users had been omitted from the abnormals. With the collagen/epinephrine cartridges, evaluating 99 normals and 70 abnormals, a value of 0.89 was obtained. This analysis entailed also aspirin users. Of 24 known aspirin users the collagen/epinephrine cartridges identified 20 that had normal closure times with the collagen/ADP cartridges. Three aspirin users had abnormal values with both cartridges, one subject was normal with both. When the traditional Ivy bleeding times were plotted as an ROC curve, an area under the curve of 0.698 was found. The data suggest that the PFA-100™ system identifies normals and abnormals (subjects with primary, platelet related hemostasis defects) with greater sensitivity and specificity than the present widely used bleeding time. The instrument is easy to use and could be adapted to routine laboratory use. The data presented are preliminary and need to be confirmed by additional testing.†Not commercially available in the U.S.A.
Keywords: primay hemostasis; bleeding time; PFA100™; Thrombostat, ADP; epinephrine